SIMULATION OF AQUIFER REMEDIATION FROM LOW-PERMEABLE LENSES BY BACK-DIFFUSION PHENOMENON - Mojtaba Dehqani Tafti (Faculty of Mining, Geology and Petroleum Engineering, 2021)
Fluid flow in a dual permeable medium (DPM) is essential in solute transport in mining and aquifer studies. In this paper, water flushing into a contaminated DPM containing fine-grained lenses with different geometries was investigated with the Lattice Boltzmann Method (LBM). The LBM model used in this study was D2Q9 with a relaxation time of 1, a cohesion value of 3 for a fluid density of 1 (mu.Lu-3). The saturated fluid in the DPM was a contaminant that usually stays in low permeable lenses and after flushing, it is leaked into the porous medium by a second fluid (water). This phenomenon is predominant when the displacing fluid has a lower concentration than the contaminated fluid. Diffusion and advection are the main mechanisms that control fluid flow in the porous medium. The results of the simulations showed: (1) advection controlled solute transport through the flushing phase, and back-diffusion occurred after the change in phase; (2) the lenses’ geometry influenced the fluid flow pattern and the remediation process. As a result, aquifer remediation strategies based on the lenses’ geometry and their permeability can help us select the appropriate environmental protection.